Optimizing a fixed-precision sequential sampling plan for adult Acrotomopus atropunctellus (Boheman) (Coleoptera: Curculionidae), new pest on sugarcane - Perez, Maria Lucia del Pilar; Isas, Marcos Gerardo; Salvatore, Analia Ruth; Gastaminza, Gerardo; Trumper, Eduardo Victor (Elsevier, 2019)
Sugarcane weevil borer, Acrotomopus atropunctellus (Boheman) (Coleoptera: Curculionidae) has been detected across all sugarcane planting areas in the Argentinian Northwest with increasing population densities. The monitoring for its occurrence and the population density usually is made by visual inspection and consequently demands much effort and time. The objectives of this study were 1) to describe the sampling distribution pattern of A. atropunctellus adults 2) to develop and validate a fixed-precision sequential sampling plan for density estimation, and 3) to find the optimum inspection time for each sampling unit. On-farm data collection was performed at sugarcane fields located in Ranchillos (Tucumán, Argentina) during 2011–2012 to 2013–2014 sugarcane growing seasons. Thirty sampling units consisting on one meter of sugarcane furrow were randomly selected at 1-wk intervals. Within each sampling unit, weevils were counted and recorded independently for five increasing examination time per sampling unit (ETSU) (2, 4, 6, 8 and 10 min). For each ETSU, the sampling distribution pattern was assessed by Taylor's power law (TPL). The average sample number (ASN) and sampling stop lines were calculated according to Green's sequential sampling model, based on TPL estimated parameters, for fixed precision levels, C = 0.1 and C = 0.25. The resampling for validation of sample plans (RVSP) program was used to evaluate the performance of the different sampling plans. Parameters a and b from TPL regressions did not vary significantly between different ETSUs. All estimates of b coefficients were significantly >1 which can indicate an aggregated sampling distribution pattern. For each precision level, Green's sequential plans predicted very similar ASN between ETSU. This was confirmed through the validation process, with the five sampling protocols providing very similar mean sample sizes and mean precision levels. Variability of these parameters from validation results did not vary significantly among the different ETSUs. The relative net precision was the only performance parameter that varied with the ETSU, with the shortest ETSU resulting in the most efficient sampling plan. We conclude that A. atropunctellus has an aggregated sampling distribution and that the fixed precision sequential sampling plan developed using Green's model and based on a two-minute inspection of the sampling unit is the most convenient choice for estimating its population density in sugarcane. Our analysis of the ETSU effect on the performance of sugarcane weevil sampling protocols could contribute to develop more efficient monitoring plans for other arthropods.